AB0706 Centre-Related Features Determine Variability of Hospital Admissions of Patients with Spondyloarthritides in Spain. (10th June 2014) - Andres, M.; Sivera, F.; Vela, P.; Pérez-Vicente, S.
Abstract : Objectives: To explore the variability in hospital admissions of patients with spondyloarthritides (SpA) in Spain, and which factors related with the centre contribute to this variability (after adjustment by patient and disease features). Methods: Descriptive cross-sectional study, part of the emAR II study performed in Spain in 2009-2010. Case notes of patients with a diagnosis of SpA and at least one visit in the Rheumatology units within the previous two years were selected using an equiprobabilistic sampling process and audited. Collected variables related to hospital admissions, clinical features (related to the SpA) and non-clinical features (related to the patient, the responsible physician, the Rheumatology unit and the hospital centre). Statistical analyses included a descriptive analysis and bivariate analysis to assess association between risk factors and admissions. Then those variables with a significant association in the bivariate analysis and/or deemed as clinically relevant or potential confounders, all were later included in a multilevel logistic regression analysis of random intercept with non-random slopes, in order to assess variability in hospital admissions between centres. Results: A total of 1, 168 patients' case notes from 45 centres were enrolled. Main SpA forms were ankylosing spondylitis (55.2%) and psoriatic arthritis (22.2%). A total of 248 admissions of 196 patients (19.2%, n=1, 020) were registered, mainly due to surgical procedures (32.7%), comorbidities (15.3%) and disease activity (12.1%). A variability of 17.6% in hospitalizations between centres was noted (Table), not explained by clinical variables (M2[A1]). This variability was attributed to hospital-related factors (M3): the number of admissions of the centre (OR 1.003, 95%CI 1.000-1.006), the existence of computer-assisted admission orders (OR 3.754, 95%CI 1.201-11.731) and the availability of ultrasound in the unit (OR 0.400, 95%CI 0.211-0.757) showed a significant association with admissions, but explained 42.9% of the variability. The risk of a patient with SpA of being hospitalized was found to double (median OR 2.086) depending on the hospital where the patient is being managed. Conclusions: Hospital admissions of patients with SpA varied widely between hospitals, in relation with centre characteristics. Further studies are needed to ascertain which specific factors are causing the variation between centres, as variables included in this study explained less than half of the variability. Acknowledgements: To César Hernández, Loreto Carmona, María Jesús García de Yébenes, Miguel Άngel Descalzo, Juan Manuel Barrio, María Auxiliadora Martín and Estíbaliz Loza, for their significant contribution in the development of the study protocol, electronic database and statistical analysis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1693